2015
DOI: 10.1093/database/bav099
|View full text |Cite
|
Sign up to set email alerts
|

NeuroTransDB: highly curated and structured transcriptomic metadata for neurodegenerative diseases

Abstract: Neurodegenerative diseases are chronic debilitating conditions, characterized by progressive loss of neurons that represent a significant health care burden as the global elderly population continues to grow. Over the past decade, high-throughput technologies such as the Affymetrix GeneChip microarrays have provided new perspectives into the pathomechanisms underlying neurodegeneration. Public transcriptomic data repositories, namely Gene Expression Omnibus and curated ArrayExpress, enable researchers to condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…For querying AD-specific gene expression data, we used previously developed database, NeuroTransDB [ 78 ], which contains highly curated meta-data information for eligible AD studies. It assembles studies from public resources namely, GEO and ArrayExpress, using a keyword based search approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For querying AD-specific gene expression data, we used previously developed database, NeuroTransDB [ 78 ], which contains highly curated meta-data information for eligible AD studies. It assembles studies from public resources namely, GEO and ArrayExpress, using a keyword based search approach.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in our recent publication [ 78 ], we have highlighted the key issues related to retrieval and reusability of the datasets from public transcriptomics archives, such as GEO and ArrayExpress. We showed that a simple keyword based search not necessarily asserts the specificity of the retrieved datasets to the queried disease or organism.…”
Section: Methodsmentioning
confidence: 99%
“…To faithfully identify the correct studies to include in such a meta-analysis strategy requires detailed, domain-specific meta-data for each study, which is only partially addressed by the MIAME standard. To enrich the available meta-data for Alzheimer’s disease gene expression studies, Bagewadi et al [ 87 ] followed a semi-automated, manually curated approach to harvest detailed and standardised annotations from the accompanying publications. The annotations are modeled using a custom RDF schema that allows in-depth assessment of the respective phenotype, the type of tissue used in an experiment, and accessory information for the donor of the tissue such as; gender, age, possible comorbidities, etc.…”
Section: Bioinformatics Methods For the Identification Of Disease mentioning
confidence: 99%
“…One study retrieved corresponding records from two biological databases, Gene Expression Omnibus and ArrayExpress, but surprisingly found the number of records to be significantly different: the former has 72 whereas only 36 in latter. Some of the records were identical, but in some cases records were in one but not the other (23). Indeed, duplication commonly interacts with inconsistency (5).…”
Section: Impact Of Duplicatesmentioning
confidence: 99%